Studi Analisis Nilai-Nilai Melayu tentang Birrul Walidayn dalam Tafsir Nur Al-Ihsan (Telaah teori Sosio-Kultural) Jurnal Ilmu Al-Qur’an dan Tafsir - Khamdani, Eep Nafis; Machmudah, Isti ‘Anatul; Fauzi, Alwi Hanifan; Rizkoh, Nur Amniar; Lafani, Ahmad Mughisul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The Malay community is widely known for upholding noble values deeply rooted in their language, behavior, and daily practices. This study investigates how these Malay cultural values are integrated into the interpretation of Surah Al-Isra’ verses 23–25 concerning birrul walidayn (dutifulness to parents) as presented in Tafsir Nur Al-Ihsan by Sheikh Muhammad Sa'id bin 'Umar al-Falimbani. The research adopts a qualitative method using content analysis and a socio-cultural approach, with data collected through library research involving primary and secondary sources. The findings reveal that the interpretation in Tafsir Nur Al-Ihsan harmoniously combines textual and contextual meanings, reflecting essential elements of Malay values such as obedience and piety, etiquette, social care, and cultural identity. These values are embedded not only in the textual interpretation but also in the behavioral guidance provided to the readers. Furthermore, the use of the Malay-Jawi language in the tafsir reinforces its accessibility and relevance for the local community. The study concludes that Tafsir Nur Al-Ihsan serves not only as a religious exegesis but also as a cultural medium that bridges Islamic teachings with local wisdom. This research contributes to the development of context-based tafsir studies in Southeast Asia and emphasizes the importance of integrating religious texts with social and cultural perspectives to foster a more grounded and dynamic understanding of Islam.